Let $a,b,c$ be positive reals such that $ab+bc+ca+abc=4$.

Then prove

$\sqrt{ab}+\sqrt{bc}+\sqrt{ca}\leq 3\leq a+b+c $

So high guys im a high schooler trying to solve this inequality. I did a few things such as try to set a> b>c and then try to generalize it but i couldn't make much progress at all. I would appreciate a clear solution to help me understand the problem in depth.

I did manage to generalize that

$\sqrt{ab}+\sqrt{bc}+\sqrt{ca}\leq a+b+c $

By using the AM-GM inequality on each of a b and c however havent made much progress in proving that the LHS is less than 3 and the RHS is greater than 3.

  • $\begingroup$ As you are new to this site, we appreciate when some work is done especialy when you desire a "very explanatory" solution. You say "I did a few things". Show them. Assuming $a>b>c$ is not enough... $\endgroup$ – Jean Marie Oct 7 '17 at 19:03
  • $\begingroup$ Do you know standard inequalities such as AM-GM-HM ? $\endgroup$ – Mastrem Oct 7 '17 at 19:04
  • $\begingroup$ The thing is i didnt understand the problem much and im having alot of trouble with it. I havent done much in terms of actually working on the problem so ................ $\endgroup$ – Mojimoji Oct 7 '17 at 19:05
  • $\begingroup$ Well, then show us your trouble :) $\endgroup$ – Mastrem Oct 7 '17 at 19:05
  • $\begingroup$ I know AM-GM yes $\endgroup$ – Mojimoji Oct 7 '17 at 19:06

AM-GM on $ab$, $bc$, $ca$ and $abc$ gives: $$1=\frac{ab+bc+ca+abc}{4}\ge\sqrt[4]{(abc)^3}\implies 1\ge abc$$ So, still using the first equation: $$ab+bc+ca\ge 3$$ Now, by AM-GM $$a^2+b^2\ge 2ab$$ $$b^2+c^2\ge 2bc$$ $$c^2+a^2\ge 2ac$$ Adding them all up and dividing by $2$ gives: $$a^2+b^2+c^2\ge ab+bc+ca$$ So now: $$(a+b+c)^2=a^2+b^2+c^2+2(ab+bc+ca)\ge 3(ab+bc+ca)\ge 9$$ From which it follows that: $$a+b+c\ge 3$$ I'll work on the other inequality when I have time

| cite | improve this answer | |
  • $\begingroup$ id really like your input too when you have the time as i found your explanation really easy to follow. $\endgroup$ – Mojimoji Oct 8 '17 at 17:17

Both inequalities we can prove by the Contradiction method.

Indeed, for the right inequality let $a+b+c<3$, $a=kx$, $b=ky$ and $c=kz$,

where $k>0$ and $x+y+z=3$.

Thus, $k(x+y+z)<3$, which gives $k<1$.

Hence, $4=ab+ac+bc+abc=k^2(xy+xz+yz)+k^3xyz<xy+xz+yz+xyz$,

which is contradiction because we'll prove now that $$4\geq xy+xz+yz+xyz$$ or $$\frac{4(x+y+z)^3}{27}\geq\frac{(x+y+z)(xy+xz+yz)}{3}+xyz$$ or $$\sum_{cyc}(4x^3+3x^2y+3x^2z-10xyz)\geq0,$$ which is true by Muirhead.

Also, we can use AM-GM. $$\sum_{cyc}x^3=x^3+y^3+z^3\geq3\sqrt[3]{x^3y^3z^3}=3xyz;$$ $$\sum_{cyc}(x^2y+x^2z)=x^2y+x^2z+y^2x+y^2z+z^2x+z^2y\geq6\sqrt[6]{x^6y^6z^6}=6xyz.$$ Thus, $$\sum_{cyc}(4x^3+3x^2y+3x^2z-10xyz)=$$ $$=4(x^3+y^3+z^3)+3(x^2y+x^2z+y^2x+y^2z+z^2x+z^2y)-30xyz\geq$$ $$\geq4\cdot3xyz+3\cdot6xyz-30xyz=0.$$

The left inequality.

Let $\sqrt{ab}+\sqrt{ac}+\sqrt{bc}>3$, $a=kx$, $b=ky$ and $c=kz$,

where $k>0$ and $\sqrt{xy}+\sqrt{xz}+\sqrt{yz}=3$.

Thus, $k(\sqrt{xy}+\sqrt{xz}+\sqrt{yz})>3$, which gives $k>1$ and $$4=ab+ac+bc+abc=k^2(xy+xz+yz)+k^3xyz>xy+xz+yz+xyz,$$ which is contradiction because we'll prove now that $$4\leq xy+xz+yz+xyz.$$ Indeed, let $\sqrt{xy}=r$, $\sqrt{xz}=q$ and $\sqrt{yz}=p$.

Thus, $p+q+r=3$ and we need to prove that $$p^2+q^2+r^2+pqr\geq4$$ or $$\frac{(p+q+r)(p^2+q^2+r^2)}{3}+pqr\geq\frac{4(p+q+r)^3}{27}$$ or $$\sum_{cyc}(5p^3-3p^2q-3p^2r+pqr)\geq0$$ or $$\sum_{cyc}(p^3-p^2q-p^2r+pqr)+2\sum_{cyc}(2p^3-p^2q-p^2r)\geq0,$$ which is true by Schur and Muirhead.

The inequality $\sum\limits_{cyc}(2p^3-p^2q-p^2r)\geq0$ we can prove also without Muirhead: $$\sum_{cyc}(2p^3-p^2q-p^2r)=\sum_{cyc}(p^3-p^2q-pq^2+q^3)=\sum_{cyc}(p-q)^2(p+q)\geq0.$$


Also, we can use the following trigonometric substitution.

Let $\sqrt{ab}=2\cos\gamma$, $\sqrt{ac}=2\cos\beta$ and $\sqrt{bc}=\cos\alpha$.

Thus, $$\cos^2\alpha+\cos^2\beta+\cos^2\gamma+2\cos\alpha\cos\beta\cos\gamma=1,$$ where $\alpha$, $\beta$ and $\gamma$ are measures of acute angles.

Hence, easy to see that $\alpha+\beta+\gamma=180^{\circ}$ and we need to prove that $$\cos\alpha+\cos\beta+\cos\gamma\leq\frac{3}{2}$$ and $$\sum_{cyc}\frac{\cos\alpha\cos\beta}{\cos\gamma}\geq\frac{3}{2},$$ which is obvious.

Done again!

| cite | improve this answer | |
  • $\begingroup$ wait how can we say k is the same for a b and c $\endgroup$ – Mojimoji Oct 8 '17 at 5:00
  • $\begingroup$ This proof is way too advanced. While i really appreciate your effort if theres a simpler way of doing it id prefer that considering ive never studied muirhead. $\endgroup$ – Mojimoji Oct 8 '17 at 5:05
  • $\begingroup$ Im very new to the site so i didnt know how to just checked and accepted your answer $\endgroup$ – Mojimoji Oct 8 '17 at 5:06
  • $\begingroup$ i dont know the muirhead inequality and how can you assume the same k for all of x y and z $\endgroup$ – Mojimoji Oct 8 '17 at 5:16
  • 1
    $\begingroup$ @Mojimoji Let $(a,b,c)=(1,0.5,05)$. Hence, Let $a=kx$, $b=ky$ and $c=kz$, where $k>0$ and $x+y+z=3$. Thus, $2=1+0.5+0.5=k(x+y+z)=3k$ and $k=\frac{2}{3}$. Similarly I can do it in the general case. I hope, it's clear now. $\endgroup$ – Michael Rozenberg Oct 8 '17 at 5:21

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.